2021
DOI: 10.3390/healthcare9060638
|View full text |Cite
|
Sign up to set email alerts
|

Face Mask Usage among Young Polish People during the COVID-19 Epidemic—An Evolving Scenario

Abstract: The usage of face masks has been mandated in many countries in an attempt to diminish the spread of SARS-CoV-2. In this cross-sectional study, we aimed to determine face mask-wearing behaviors and practices in 1173 young Polish people during the second wave of the COVID-19 epidemic in October 2020. The majority of respondents (97.4%) declared that they wore face masks in areas/situations where it is mandatory. The most common types of utilized face masks were cloth masks (47.7%) and surgical masks (47%), follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
7
0
2
Order By: Relevance
“…Moreover, in another study conducted through public webcams in the United States, United Kingdom, and Ireland, 51% of the participants wore masks correctly [ 37 ]. The critical point is that researchers have shown that the correct and widespread use of facemasks among the general population [ 38 , 39 ] and nurses [ 40 ] contributes significantly to limiting the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in another study conducted through public webcams in the United States, United Kingdom, and Ireland, 51% of the participants wore masks correctly [ 37 ]. The critical point is that researchers have shown that the correct and widespread use of facemasks among the general population [ 38 , 39 ] and nurses [ 40 ] contributes significantly to limiting the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the number of registered GBS cases, while underestimated, has fallen during the COVID-19 pandemic; on the other hand, altered social conduct is observed. Due to changes in social behavior, such as social distancing and the use of personal protective equipment and hygienic procedures, the prevention of infectious diseases, known as triggers of GBS, has increased [37,38]. Recent comments characterizing GBS as occurring in occasional clusters can be found as well [39].…”
Section: Discussionmentioning
confidence: 99%
“…A Polish study, based on interviews, found that 46.2% of young adults used fabric masks, with women more likely to wear this type (48.6% women vs. 36.5% men) [38]. A second study, also of Polish youths, found a similarly high level of fabric mask use (47.7%), but without the previously noted pronounced gender bias (48.6% women vs. 45.1% men) [37]. A survey of university students in Vietnam found that cloth masks were worn by 23.1% of the respondents [39].…”
Section: Discussionmentioning
confidence: 96%
“…include observations in Poland [37,38], Vietnam [39], Bali (Indonesia) [40], Nigeria [41], India [42], Morocco [43], and Iran [44]. None of these, however, can be extrapolated to the Australian situation given cultural differences in the observed communities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation